2021
DOI: 10.1021/acs.jchemed.1c00794
|View full text |Cite
|
Sign up to set email alerts
|

CADMIO: Creating and Curating an Educational YouTube Channel with Chemistry Videos

Abstract: YouTube is one of the most known and used social networks among students in the world, and undergraduate chemistry students are no exception. Undeniably, YouTube can offer several advantages for complementing university lessons in an asynchronous manner. There are many chemistry channels available on the internet; however, they are mainly too general or run by nonprofessionals, resulting in misconceptions or inaccuracies that lead to student confusion. In this contribution, we present CADMIO, a peer-to-peer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
16
0
3
Order By: Relevance
“…Since the COVID-19 pandemic, the use of educational YouTube videos has become more prevalent, meaning it is even more essential that teachers are able to select appropriate multimedia tools to support student learning . Since this project’s inception and the bulk of data collection, which largely occurred before the start of the COVID-19 pandemic, there have been numerous studies that detail the use and efficacy of online or other multimedia videos in the classroom. Some of these studies apply more generally to video-oriented classrooms such as flipped classrooms which use preclass materials (PCM) to introduce content. In one case, creators included in our study were specifically called out as potential sources for PCM . We maintain that, particularly in this new era of video content usage, not only are content creators responsible for generating pedagogically sound content, but educators also have a responsibility to attend to principles of how students learn when selecting relevant content to include in their courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the COVID-19 pandemic, the use of educational YouTube videos has become more prevalent, meaning it is even more essential that teachers are able to select appropriate multimedia tools to support student learning . Since this project’s inception and the bulk of data collection, which largely occurred before the start of the COVID-19 pandemic, there have been numerous studies that detail the use and efficacy of online or other multimedia videos in the classroom. Some of these studies apply more generally to video-oriented classrooms such as flipped classrooms which use preclass materials (PCM) to introduce content. In one case, creators included in our study were specifically called out as potential sources for PCM . We maintain that, particularly in this new era of video content usage, not only are content creators responsible for generating pedagogically sound content, but educators also have a responsibility to attend to principles of how students learn when selecting relevant content to include in their courses.…”
Section: Discussionmentioning
confidence: 99%
“…28−30 In one case, creators included in our study were specifically called out as potential sources for PCM. 28 We maintain that, particularly in this new era of video content usage, not only are content creators responsible for generating pedagogically sound content, 31 but educators also have a responsibility to attend to principles of how students learn when selecting relevant content to include in their courses. This may take the form of considering cognitive load theory when attending to video creation, or other theories which support learning, such as metacognition.…”
Section: Implications For Chemistry Teachingmentioning
confidence: 99%
“…For example, in 2019, YouTube was used by 73% of Spaniards between 16 and 30 years old and Instagram by more than 65% of people in the same age group . Furthermore, students use video-sharing platforms such as YouTube, not only for recreational purposes but also to gather information and the formation of chemical topics. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a comprehensive understanding of the result of a physicochemical calculation depends on how units influence the answer . In this regard, SI units are meant to be used together with the quantity calculus, allowing dimensional analysis and unit cancellation, and thus providing a double-check on the correctness of a calculation. , However, it has been repeatedly observed that while this is a crucial topic, first-year undergraduate students do not master it completely, generating further issues with more advanced content. , In general, students are faced with the essential assignment of learning and memorizing a broad variety of physicochemical units without necessarily understanding the relationship between the physical quantity, its unit, and its symbol, much less how it is measured experimentally. This is particularly evident when SI units are introduced for the first time in college courses for all branches of chemistry. , To tackle this troubling issue, some original efforts have been done. , Especially interesting is the work of Davies, who proposes a roadmap to solve stoichiometry problems emphasizing dimensional analysis and the use of units to verify the solving process. This roadmap tends to favor active learning and reasoning from simple and easy-to-understand diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…14−19 This is particularly evident when SI units are introduced for the first time in college courses for all branches of chemistry. 11,20 To tackle this troubling issue, some original efforts have been done. 21,22 Especially interesting is the work of Davies, 4 who proposes a roadmap to solve stoichiometry problems emphasizing dimensional analysis and the use of units to verify the solving process.…”
Section: Introductionmentioning
confidence: 99%